Reservoir Characterization using seismic and well Log Data - Kushwaha, Prabodh Kumar (IIT (BHU), Varanasi, 2020)
Full Abstract is available in the attachment
This thesis was submitted by Pramodh Kumar Kushwaha Roll No. 15151005 Department of Mining Engineering Indian Institute of Technology (Banaras Hindu University Varanasi-221005 India Supervised by Prof. Piyush Rai
Keywords: Seismic; Log Data